Психологічний зміст комунікативної агресії у дівчат та юнаків студентського віку - Білюченко, Ю. М.; Biliuchenko, Yu. M. (Вісник Львівського університету. Сер.: Психологічні науки. - 2021. - Вип.11. - С. 23-28, 2021)
Розглянуто проблему комунікативної агресії у студентської молоді. Зазначено, що прояви агресії в комунікативній сфері є доволі розповсюдженим та небезпечним явищем у психологічному сенсі. Комунікативна агресія є усвідомленим актом заподіяння шкоди іншій особі через вербальні форми. Виявлено інтегральні форми комунікативної агресії у студентської молоді з урахуванням гендерних розбіжностей. Наголошено, що попри схожість параметрів інтегральних форм комунікативної агресії у дівчат та юнаків студентського віку, були визначені значущі відмінності та тенденції.

The article presents a brief review of the scientific literature on the problem of communicative aggression in student youth. Theoretical analysis revealed that manifestations of aggression in the communicative sphere are quite common and dangerous in the psychological sense. Foreign and domestic scholars agree that communicative aggression is a conscious act of harming another person through verbal forms. The aim of the study was to identify the specifics of integrated forms of communicative aggression in students, taking into account gender differences. The study sample consisted of 40 students aged 18 to 20 years. The first group consisted of 20 girls, the second group included 20 boys. To achieve this goal, we used the method of “Determining the level of integrated forms of communicative aggression” by V. Boyko. The results were described by the following parameters: spontaneity of aggression, inability to inhibit aggression, inability to transfer aggression to activities or inanimate objects, anonymous aggression, provocation of aggression in others, tendency to repulsed aggression, self-aggression, ritualization of aggression, tendency to infect aggression aggression, retribution for aggression. Mathematical and statistical processing of the results was performed using Student’s t-test for independent samples. An empirical study found that student girls have difficulty inhibiting aggression and a certain lack of ability to quickly master their emotional state. They tend to provoke and repel aggression in situations that are unfair to them, which pushes them to incite others to aggression in order to achieve their own goals. It was found that girls have higher rates of aggression in almost all studied parameters compared to boys, which indicates a greater ability of girls to demonstrate aggressive behavior in the process of communication and interaction with others. Spontaneous manifestations of aggression are more typical for boys of student age, which, at the same time, is mainly due to stereotypical and ritual reasons, which allows to state less involvement of integral forms of communicative aggression in shaping behavioral reactions of these subjects in communication.

Рассмотрена проблема коммуникативной агрессии у студенческой молодежи. Отмечено, что проявление агрессии в коммуникативной сфере является довольно распространенным и опасным явлением в психологическом смысле. Коммуникативная агрессия является осознанным актом причинения вреда другому лицу через вербальные формы. Выявлены интегральные формы коммуникативной агрессии у студенческой молодежи с учетом гендерных различий. Отмечено, что, несмотря на сходство параметров интегральных форм коммуникативной агрессии у девушек и юношей студенческого возраста, были определены значительные различия и тенденции.
Psychological content of communicative aggression in girls and boys of student age
Білюченко, Ю. Психологічний зміст комунікативної агресії у дівчат та юнаків студентського віку / Юлія Білюченко // Вісник Львівського університету. Сер.: Психологічні науки. - 2021. - Вип.11. - С. 23-28. - DOI: https://doi.org/10.30970/PS.2021.11.4.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; агресія; aggression; агрессия; агресивна поведінка; aggressive behavior; агрессивное поведение; гендер; gender; комунікативна агресія; communicative aggression; коммуникативная агрессия; студенти; students; студенты